Diaqua(5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane)nickel(II) tetracyanidonickelate(II) - Zhang, Qian (International Union of Crystallography, 2009)
In the title complex, [Ni(C(16)H(36)N(4))(H(2)O)(2)][Ni(CN)(4)], the [Ni(teta)(H(2)O)(2)](2+) cations (teta = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane) and [Ni(CN)(4)](2−) anions are arranged in an alternating fashion through electrostatic and N—H⋯N and O—H⋯N hydrogen-bonding interactions, forming a two-dimensional layered structure. Adjacent layers are linked through weak van der Waals interactions, resulting in a three-dimensional supramolecular network.